THU0069 Influence of The Difference between Patient and Physician Global Assessment on Disease Activity Status in High and Lower Income Countries: Data from The Meteor Database. (15th July 2016) - Bergstra, S.A.; van den Berg, R.; Chopra, A.; Da Silva, J.A.P.; Vega-Morales, D.; Govind, N.; Allaart, C.F.; Landewé, R.B.M.
Abstract : Background: Patients with rheumatoid arthritis (RA) score their global disease activity (ptGD) on average higher than physicians (phGD). This difference can vary between countries with high and lower gross national income (GNI) 1 . Also, patients with RA in lower GNI countries have less access to biologic and synthetic DMARDs 2 . With targeted treatment aiming at low disease activity (LDA) or remission, this could influence treatment. Objectives: To compare differences between ptGD and phGD in high and lower GNI countries and to assess how these potential differences influence disease activity measures. Methods: RA patients included in the METEOR (Measurement of Efficacy of Treatment in the Era of Outcome in Rheumatology) database were selected from countries ≥30 patients with >1 visit, available phGD and DAS or DAS28. Countries were divided in high and lower GNI (World Bank definition, high income GNI per capita ≥12746). ptGD and phGD were measured on a 100mm visual analogue scale (100 worst score); A difference ≥20 mm between ptGD and phGD (GDdif=ptGD–phGD) was considered clinically relevant. Next, ptGD was replaced by phGD in the DAS and DAS28, to assess potential changes in the number of patients in LDA or remission. Results: From high GNI countries, 6928 patients were included, from lower GNI countries 5136 patients. DAS was available in 10420 patients (6179 from high GNI countries), DAS28 in 11173 patients (6839 from high GNI countries). Patients from lower GNI countries had higher disease activity [mean (SD) DAS28 4.6 (1.8) vs 3.4 (1.8); DAS 2.5 (0.9) vs 1.8 (0.9)], longer disease duration at diagnosis [55 (69) vs 27 (59) weeks] and less often reached LDA [DAS28 49% vs 75%; DAS 20% vs 48%] or remission [DAS28 7% vs 32%; DAS 20% vs 48%] than patients from high GNI countries. Compared to high GNI countries, in lower GNI countries, more patients had a GDdif ≥20 mm with ptGD>phGD (44% vs 30%) and fewer patients had a GDdif <20 mm (47% vs 67%). Also, more patients had a GDdif ≥20 mm with ptGD<phGD (9% vs 3% in lower vs high GNI countries). Replacing ptGD by phGD resulted in a mean (SD) change in DAS and DAS28 of 0.09 (0.1) and 0.4 (0.6) in high GNI countries and 0.9 (0.1) and 0.4 (0.7) in lower GNI countries. For both DAS and DAS28, the percentage of patients changing disease activity status is low in all countries [mean change in DAS LDA 4.8%, remission 3.3%; DAS28 LDA 6.4%, remission 4.4%], with most patients gaining LDA or remission (Fig. 1 ). Conclusions: Compared to high GNI countries, patients from lower GNI countries had higher disease activity and less often reached LDA or remission. Clinically relevant differences between ptGD and phGD existed in more than 1/2 of the patients in lower GNI countries and 1/3 of the patients in high GNI countries, thereby influencing disease activity stronger in lower GNI countries as compared to high GNI countries. These results indicate a different access to good RA care in lower and high GNI countries. References: Gvozdenović et al ARD 2014;73(Suppl2):336 Putrik et al ARD 2015; doi:10.1136/annrheumdis-2015-207738 Disclosure of Interest: None declared